A Study Changes of Some Bichemical Parameters During Experimental Infection with Eimeria tenella in Local and Foreign Breeds of Chicken - K. A., Dawood; K. T., AL-Shaibany (Al-Qadisiyah Journal of Pure Science, 2017)
The study conducted in Animal house of the department of Biology, College of Education, Al-Qadisiya University during the period from 1/9/2013 to 1/9/2014. The study diagnosed the parasite of E.tenella in naturally infected chickens in poultry farms. E.tenella was isolated from the infected cases in Vet. hospital and Vet. clinics.Then,the cases diagnosed initially in the laboratory direct examining stool by ordinary microscope and the positive cases were recorded and diagnosed by yusing the technique of Conventional Polymerase Chain Reaction(PCR). There are 315 cases of infected chicken which examined and the results showed that (186 out of 315) stool Samples,59%, The experimental infection for each experiment was done in age 21 day with dosage of (5Ã—104) grown oocysts/chicken for E.tenella in two types of chickens(Ross and local breed) Also,two groups of uninfected chickens (control)for the sake of comparison. The biochemical parameters of blood serum in Ross chickens showed that significant decrease (p<0.05) in glucose concentration (156.9811mg/100ml in the fourth week of infection), cholesterol concentration and total protein concentration (62.11, 1.92 mg/ 100ml respectively in the fifth week of infection).Also, Uric acid increased significantly (p<0.05) to reach(10.19mg / 100ml) in the fourth week of infection in comparison of uninfected chickens of the control group. The biochemical parameters of blood serum in local breed chicken showed the significant decrease (p<0.05) in glucose concentration (169.60mg/100ml in the fifth week of infection) , cholesterol concentration and total protein concentration (70.89 , 2.25mg/100ml respectively in the fourth week of infection). Uric acid increased significantly (p<0.05) to reach (7.62mg/100ml) in the fifth week of infection in comparison with the control group.